The implementation and effect of sasi on coconut (Cocos nucifera L.) harvest products in southern Buru, Indonesia - Tuhumuri Evelin; Sancayaningsih Retno Peni; Setiaji Bambang; Usman Sunyoto (Oilseeds and fats, crops and lipids, 2020)
Coconut (Cocos nucifera L.) is common plant for the Moluccan farmers to apply local wisdom in cultivation, called sasi. This study describes sasi implementation of coconut cultivation in South Buru and its effects on the quality of the coconut harvest. The research was conducted by field observation and interviews. Data were obtained from coconut trees aged 16–25 years and > 30 years. There are two common methods of cultivation through sasi, religion-based permission (local church) and traditional sasi. Both forms of sasi have different indications. On the basis of the sasi system, coconut plantations cannot be penetrated for six months (a spell prohibiting access to the crop) and harvesting only takes place after the end of the sasi period (avoiding any risk of theft of the fruit). Yields on the 16–25-years-old trees had a weight of endosperms of 243–378 g and a thickness of the coconut endosperm of 9.2–12.2 mm over the monitored 10–18 months fruit age period, each showing a bell-shaped variation with a maximum for about 13 months old fruits. Yields on > 30-years-old trees group showed the same pattern. Thus, although sasi is useful for protecting the coconut fruit before harvesting, the implementation of coconut sasi for six months ultimately decreases the quality of the crops and postpones the best harvest time. Therefore it is recommended that the implementation of coconut sasi in South Buru be adjusted with the biological timing of coconut ripening.